2022
DOI: 10.3390/pathogens12010044
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Unveils the Pervasiveness and Diversity of Prophages Infecting Erwinia Species

Abstract: Prophages are abundant elements integrated into bacterial genomes and contribute to inter-strain genetic variability and, in some cases, modulate the environmental behavior of bacteria, such as pathogen virulence. Here, we described prophage occurrence and diversity in publicly available Erwinia genome assemblies, a genus containing plant pathogens. Prophage-like sequences were identified and taxonomically classified. Sequence diversity was analyzed through intergenomic similarities. Furthermore, we searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…We find that there were, on average, 4 prophage-like elements encoded per genome across the 590 isolates of P. syringae, demonstrating the abundance of prophage-like elements in the genomes of these isolates (Figure 5). This average number is comparable to other phytopathogenic bacteria such as Erwinia amylovora, which also carries a panel of 4 prophage-like elements per genome (36). We further observed that the average number of prophage-like elements, phage defenses and effectors encoded within both the genome and the mobilome differs across the phylogroups.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We find that there were, on average, 4 prophage-like elements encoded per genome across the 590 isolates of P. syringae, demonstrating the abundance of prophage-like elements in the genomes of these isolates (Figure 5). This average number is comparable to other phytopathogenic bacteria such as Erwinia amylovora, which also carries a panel of 4 prophage-like elements per genome (36). We further observed that the average number of prophage-like elements, phage defenses and effectors encoded within both the genome and the mobilome differs across the phylogroups.…”
Section: Discussionsupporting
confidence: 68%
“…For other plant-associated bacteria specifically, this number has been shown to be as high as 10 mechanisms for some Ralstonia and Xanthomonas isolates (34). In sharp contrast to other bacterial species (35,36), and even other Pseudomonads, CRISPR-Cas does not appear to be an important phage defense strategy in the P. syringae species complex (37,38). Instead, we demonstrated that P. syringae relies on other defense mechanisms, such as restriction enzymes and abortive infection strategies, to cope with phage predation.…”
Section: Discussionmentioning
confidence: 99%